Next-generation anti-DLL3 radiopharmaceuticals targeting high-grade neuroendocrine lung and prostate cancers - Salomon Tendler; Roberto De Gregorio; Paul Balderes; Alexa L. Michel; Tran T. Hoang; David Bauer; Kathryn M. Tully; Joshua A. Korsen; Ivo C. Lorenz; Abdul G. Khan; Lukas Carter; Olivia Vergnolle; et al. (Proceedings of the National Academy of Sciences, 2026)
Delta-like ligand 3 (DLL3) is a tumor-selective cell surface protein upregulated in high-grade neuroendocrine tumors, including small-cell lung cancer (SCLC) and neuroendocrine prostate cancer (NEPC). Here, we report on the development of anti-DLL3 radioimmunoconjugates for use as either a diagnostic imaging tracer based on the positron-emitter zirconium-89 ( 89 Zr) or a therapeutic agent utilizing the beta-emitter lutetium-177 ( 177 Lu). To begin, we generated a panel of human monoclonal antibodies targeting human DLL3 by immunizing transgenic mice engineered with a human immunoglobulin repertoire. The panel was extensively screened to identify high-affinity internalizing monoclonal antibodies (mAbs) recognizing a diversity of DLL3 epitopes. Select mAbs were reformatted as fully human Fab-arm exchange-deficient IgG4 to reduce effector function and then produced by recombinant methods. A pilot immunoPET study was performed in athymic female nude mice bearing human NCI-H82 SCLC tumors to nominate a lead candidate. ImmunoPET identified [ 89 Zr]Zr-DFO-TDI-Y-010 as the top-performing diagnostic tracer, with excellent in vivo biodistribution and tumor-to-background-organ ratios consistently >4. Therapeutic studies with [ 177 Lu]Lu-CHX-A"-DTPA-TDI-Y-010 demonstrated strong antitumor effects, significantly improving ( P <0.05) overall survival compared with the benchmark clone [ 177 Lu]Lu-CHX-A"-DTPA-SC16.56 in two SCLC tumor models (NCI-H82 and Lu149) and achieving comparable overall survival in a NEPC tumor model.